PROMOTING PATRIARCHAL POLITICS IN DAPHNE DU MAURIER’S REBECCA - Thohiriyah Thohiriyah (Institut Seni Indonesia Yogyakarta, 2020)
Abstract: This paper aims to analyze a patriarchal politics performed by the male antagonist named Maxim de Winter in his life of domestic partnership with a female protagonist, Rebecca, elucidated in Daphne du Maurier’s novel entitled Rebecca. The concept of promotion of patriarchal domination is done through deconstructive narration. At first, the novel constructs a narration by putting the woman in a privileged position. However, this position is later dismantled by male domination. This paper employs some methods consisting of close reading, qualitative analysis, and deconstructive analysis. The result shows that woman’s privileged position is only used as a medium for a man to prove his domination and promote patriarchal politics in the form of power struggle. Key words: patriarchal politics, power, Rebecca